Obelix and Co. - Goscinny, frey50; Uderzo (Greenwich, Connecticut Dargaud Publishing International, LTD., 1978)
Watch out! Julius Caesar has devised his most cunning attack yet on the indomitable Gauls. He has sent Caius Preposterus, a graduate of the Latin School of Economics, to corrupt them by introducing big business into their little town. But will wealth and success bring the Gauls happiness ... or trouble?
Keywords: Comic book strips